On the Parallel Simulation of Microparticle Capture in Axial Magnetic Filter - Hournkumnuard, Kanok; Pornjarungsak, Witchaya; Chantrapornchai, Chantana (Agriculture and Natural Resources, 2015)
A parallel algorithm was developed to simulate the capture of weakly magnetic microparticles by parallel ferromagnetic wires randomly distributed in an axial magnetic filter. The problem of microparticle capture was considered within a representative cylindrical cell composed of a representative wire and a surrounding fluid medium. The radius of the cell relative to the wire was determined by the volume fraction of the wires contained within the filter. The magnetic and axial fluid flow fields around the representative wire were determined by the effective medium and the multi-wire models, respectively. All possible trajectories within a representative cell were calculated and analyzed to evaluate the filter efficiency. The number of trajectories was quite large and it took more than 1 hr to obtain the filter efficiency for a set of operating parameters. To speed up the simulation, the work was implemented using parallel programming based on OpenMP. The accuracy of the results was verified against the sequential version. The simulation system was composed of three modules: the user interface module which obtains the operating parameters from the user, the computing module and the graphical display module. The maximum gain was 5.27 times faster and the predicted capture areas and capture efficiencies from the sequential and parallel programming agreed with each other.